PENGGUNAAN MEDIA WORDWALL UNTUK MENINGKATKAN KETERLIBATAN DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI KELAS X 3 SMA NEGERI 1 RANTAU SELATAN - Zulfa, Indana (Universitas Muhammadiyah Tapanuli Selatan, 2025)
In the learning process, it should be conducted in a two-way manner or requires active participation and involvement of students as this is a key factor in achieving optimal learning outcomes. Therefore, innovations in the learning process to be implemented are necessary. After observing the conditions in class X 3 of SMA Negeri 1 Rantau Selatan, which still showed low levels of learning involvement, the researcher implemented the learning media Wordwall to increase participation, which will ultimately also improve the learning outcomes of the students. The research method used in this study is classroom action research (PTK) which is conducted in 2 cycles, with each cycle consisting of one meeting. The results obtained show that Wordwall has a significant impact on improving student involvement and learning outcomes, which achieved a score of 50% in cycle I and experienced a significant increase in cycle II as much as 83,3%